Rheological modelling of dispersions of casein micelles considered as microgel particles - Olivares, María Laura (2013)
Rheological behavior of dispersions of casein micelles (CM) was predicted through a viscosity model  in which CM were considered as microgel particles. A simple structure for CM composed of a spherical core with a brush of kappa-casein was considered. An explicit relationship between viscosity and shear stress allows obtaining key parameters such as the packing fractions corresponding to the shear stress limits and the critical shear stress closely related to the total interaction potential between two CM. The analysisof the model parameters fitted from experimental viscosity curves indicates that CM at concentrated regime behave as soft spheres. In addition, the model provides the pair interaction energy between CM directly from rheometric data. The values obtained agree with a DLVO-like theory previously proposedfor CM. Indeed, using independent experimental data and parameters, it was possible to cross check both models. The results obtained are very promising for studying CM dispersions as colloidal systems and the stability of dairy products under different physicochemical environments.